The effect of electro-magnetic-energy-regulation therapy on subjective sleep among elite players in Norwegian women's football - Moen, Frode; Pettersen, Svein Arne; Mosleth, Ellen F. (Frontiers in Sports and Active Living, 2024)
The current study investigated if Bio-Electro-Magnetic-Energy-Regulation (BEMER) therapy is affecting subjective sleep among a sample of 21 elite female football players in a Norwegian top series club. Subjective sleep was measured each day over a period of 273 consecutive days by using a smartphone application, PM Reporter Pro, which scheduled push messages to remind the participants to report sleep every morning. The study was conducted as a quasi-experimental design, with a control period before the introduction of BEMER therapy that lasted for 3 months, followed by an intervention period where BEMER therapy was used that lasted for 5 months. The collected data from the players in the control period served as their control compared to the data collected from the players in the intervention period. Analyses of variance (ANOVA) with False Discovery Rate adjusted p-values show that subjective sleep duration and subjective sleep quality are significantly reduced on game nights, both in the control period and in the experiment period. The results also show that subjective sleep duration and subjective sleep quality significantly increase in the experiment period compared to the control period. The findings indicate that BEMER therapy might serve as a tool to improve sleep.